2012
DOI: 10.1111/j.1466-7657.2012.01013.x
|View full text |Cite
|
Sign up to set email alerts
|

Professional identity and nursing: contemporary theoretical developments and future research challenges

Abstract: Finally, a call for longitudinal studies of students to graduates, using conceptually derived and psychometrically proven instruments capable of detecting the subtle changes in the construct over time, is recommended. Further empirical research into the theoretical concepts that underline professional identity, and the factors that influence changes in this important construct in nursing, is required. Ultimately, the practical relevance of such research will lie in the potential it provides for enhanced nursin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
243
0
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(261 citation statements)
references
References 47 publications
(83 reference statements)
6
243
0
12
Order By: Relevance
“…More recently, other authors (6) have also corroborated this need to build up a professional identity. Although the characteristics of such identity can change over time, the nurse identification remains a powerful force, granting her recognition within a broader social group.…”
mentioning
confidence: 76%
“…More recently, other authors (6) have also corroborated this need to build up a professional identity. Although the characteristics of such identity can change over time, the nurse identification remains a powerful force, granting her recognition within a broader social group.…”
mentioning
confidence: 76%
“…This finding was troubling. Although Ware (2008) found that students enter into a nursing program with a beginning professional self-concept, experts suggest that pre-licensure education should be a transformative experience that supports professional identity formation (Benner et al, 2010;Johnson et al, 2012;NLN, 2010). Students at the study institution have frequently described how the senior Capstone experience of working directly with an experienced RN preceptor helped them integrate the knowledge, skills, and attitudes previously learned.…”
Section: Discussionmentioning
confidence: 99%
“…Professional identity is intertwined with and arises from professional self-concept, defined as how nurses think and feel about their abilities (Johnson, Cowin, Wilson, & Young, 2012). Both professional identity and self-concept formation are thought to be developmental processes that begin before pre-licensure education and continue throughout a career, often becoming more stable with time (Cowin, 2001;Cowin, Craven, Johnson, & Marsh, 2006;Hensel & Stoelting Gettlefinger, 2011;Johnson et al, 2012;Cronenwett et al, 2007;Ware, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Many students arrive on the first day of the course as having already commenced professional identity development. 43,44 This would be especially true of students who seek employment in pharmacies before starting formal university training. 45 However, once the student commences study, subsequent professional identity development may be delayed until the scientific basis to pharmacy practice has been mastered.…”
Section: Professionalization and Identitymentioning
confidence: 99%